2016
DOI: 10.11124/jbisrir-2016-002219
|View full text |Cite
|
Sign up to set email alerts
|

The influence of workplace culture on nurses’ learning experiences

Abstract: An optimal workplace culture is central for nurses to experience valuable and relevant learning in the workplace. To emphasize the importance of nurses' learning in the workplace, working and learning is understood as an integrated experience. Consequently, a dual system that enables nurses to demonstrate accountability for their own learning, along with clear organizational and educational systems, is required to demonstrate the value in nurses' learning and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…| 3989 organisational culture that values learning provides sufficient staffing, and organisational access to CPD can promote learning and development (Coventry, Maslin-Prothero, & Smith, 2015;Davis, White, & Stephenson, 2016). Overall, however, the effects of CPD interventions within healthcare settings are not well documented.…”
Section: Welp Et Almentioning
confidence: 99%
“…| 3989 organisational culture that values learning provides sufficient staffing, and organisational access to CPD can promote learning and development (Coventry, Maslin-Prothero, & Smith, 2015;Davis, White, & Stephenson, 2016). Overall, however, the effects of CPD interventions within healthcare settings are not well documented.…”
Section: Welp Et Almentioning
confidence: 99%
“…In support of this explanation, our figure is in agreement with a Nigerian study (46.9% of its participants received such training), which included participants from a TB referral hospital [ 37 ]. Several studies have demonstrated the significant contributions workplace learning and self-education have in improving the knowledge and skills of HCWs [ 38 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Workplace culture has the potential to have a significant impact on the learning experience of students, to provide context for workplace culture it is useful to provide a description: Ross-Walker, Rogers-Clark, & Pearce, 2012, 3084 These two levels were articulated in this meta-synthesis. Davis, White, and Stephenson (2016) conducted a systematic review to explore the influence of workplace culture on nurses learning experiences, although focused on nursing the findings could be transferred to midwifery. The review identified two main themes these were organisational influence and relational dynamics, which compare with the findings of this meta-synthesis.…”
Section: Discussionmentioning
confidence: 99%